Case report: immunotherapy successfully treated brain metastasis in intrahepatic cholangiocarcinoma and literature review - Xie, Peiyi; Guo, Lei; Zhang, Bo; Xu, Yongfeng; Song, Qi; Shi, Hongcheng; Ye, Qinghai; Li, Hui; Xiao, Yongsheng (Frontiers in Oncology, 2022)
Brain metastasis from intrahepatic cholangiocarcinoma (iCCA) is extremely rare and no standard therapeutic strategy has been established. Camrelizumab is a programmed cell death protein 1 (PD-1) inhibitor that has been widely studied in treating liver cancer. Combined immunotherapy and targeted therapy are a promising approach for treating advanced iCCA. Despite immune checkpoint inhibitors (ICIs) based neoadjuvant therapy on iCCA has shown a high response rate and resection rate, few report has shown the therapeutic efficacy of immunotherapy in treating brain metastasis from iCCA. Although PD-1 inhibitors such as camrelizumab are increasingly applied in clinic practice to treat multiple malignancies including iCCA, to the best of our knowledge, we report the first case of an iCCA patient with brain metastasis successfully treated with a combined immunotherapy and targeted therapy. The patient is a 54-year-old man with metastatic iCCA in brain treated though camrelizumab plus lenvatinib therapy with a significant response. By the time of writing, he has had a progression-free survival of 17.5 months and did not experience any severe side effects related to this therapy. Camrelizumab plus lenvatinib therapy showed favorable efficacy and manageable toxicity for this patient with advanced iCCA and could be of interest for more prospective randomized trials to further verify the potential clinical benefits.